Turnera spicata: a new species of Turneraceae (Passifloraceae s.l.) from the Brazilian Atlantic Forest - Rocha, Lamarck; Arbo, Maria Mercedes; Ribeiro, Patrícia Luz (Phytotaxa, 2018)
Turnera spicata, a new species from the Atlantic Forest of the state of Espírito Santo, Brazil, is described and illustrated here. The new species belongs to the ser. Capitatae, it can be recognized by leaves with 1–2(–3) pairs of basilaminar nectaries, bracteoles lanceolate, inflorescence spike-like abbreviated raceme, corolla white with yellow base and fruits with verrucose epicarp. Turnera spicata is morphologically compared with the closer species, T. albicans.